Production of fructo-oligosaccharides from the enzymatic conversion of coconut sugar catalyzed by fructosyltransferase in a batch reactor - Noormazlinah, Ahmad (2010)
This thesis discusses the maximization of fructooligosaccharides (FOS) production from a novel substrate coconut sugar as a new source of sucrose. The enzymatic reaction has been performed in batch reactor with enzyme which is fructosyltransferase (FTase). To elucidate the study, two phases of framework has been carried out which are characterization of materials and experimental work. The materials that have been characterized are coconut sugar, FTase and FOS for qualitative and quantitative analysis purposes. The spectral analysis of the materials has been studied by using Fourier Transform Infra Red (FTIR) to determine the functional group of each material and obtained that coconut sugar and FOS subsist of carbohydrate family while FTase contains complex of protein compounds. Coconut sugar contains of 71% sucrose for its total sugar. It is leads from other coconut parts (coconut water and coconut milk) that approved as the most suitable substrate of the study. The molecular weight of FTase is 142 kDa with 401 U/mL of enzyme activity while it is more stable between 50 to 60 oC and pH 5.5. The experimental work initially has been carried out with six reaction parameters (coconut sugar concentration, enzyme concentration, temperature, pH level, reaction time and agitation speed) was performed to facilitate the appropriate range prior to conducting a fractional factorial design approach. The initial screening performed in batch reactor using two-level fractional factorial design, indicated that reaction temperature and coconut sugar concentration were significant factors in FOS production. All these significant factors were then optimized using RSM in order to maximise the FOS concentration and conversion yield. The FOS concentration and conversion yield after optimization were 243.23 g/L and 32.52%, respectively as compared to the initial FOS concentration and conversion yield (197.31 g/L and 28.14%), indicating an improvement of 45.92 g/L and 18.83%. The optimum conditions of reaction temperature and coconut sugar concentration were found to be at 54.34 ºC and 750.73 g/L. Finally, the self-fabricated 10L batch reactor has been utilized for scale up purposes consecutively for industry application which resulted 30.03% for the yield of FOS. It is proved that the equation is applicable for industrial scale with difference of 2% with lab scale.